ZnCdS / La2O2CO3 composite photocatalytic material and preparation method thereof

CN122912931APending Publication Date: 2026-10-16HARBIN UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611344562.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-01
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

尽管如此,目前已报道的ZnCdS基光催化材料体系仍较为有限,开发光催化产氢性能优良的新型ZnCdS基复合光催化材料,仍然是该领域具有研究价值的重要课题

Benefits of technology

[0015]Compared with related technologies, this invention successfully prepared a ZnCdS/La2O2CO3 composite photocatalytic material by combining ZnCdS with La2O2CO3. Specifically, this invention uses a solvothermal method to grow a ZnCdS precursor in situ on the surface of La2O2CO3. In the resulting composite material, particulate ZnCdS is uniformly distributed on the surface of nanoflower-like La2O2CO3, and the two components form a close contact at the interface, constructing a band-matched heterojunction structure. Under simulated sunlight irradiation, this heterojunction structure can generate a built-in electric field at the interface, driving the directional transfer of photogenerated electrons and holes along a specific direction, effectively suppressing the recombination of photogenerated carriers, and significantly improving the utilization rate and lifetime of photogenerated electrons. At the same time, the unique 4f electron structure, oxygen storage capacity, and alkaline surface of La2O2CO3 provide abundant active sites for the reaction, further promoting the adsorption and activation of reactants on the catalyst surface. The synergistic effect of the above-mentioned multiple factors has significantly improved the absorption and utilization efficiency of sunlight by the ZnCdS/La2O2CO3 composite photocatalytic material prepared in this invention. Its photocatalytic water splitting hydrogen production performance is significantly better than that of single ZnCdS and single La2O2CO3 materials, providing a practical and feasible technical path for developing efficient and stable new photocatalytic hydrogen production materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912931A_ABST
    Figure CN122912931A_ABST
Patent Text Reader

Abstract

The application provides a ZnCdS / La2O2CO3 composite photocatalytic material and a preparation method thereof, relates to the technical field of photocatalytic materials, and the preparation method comprises the following steps: preparing La2O2CO3 material and a ZnCdS precursor solution; the La2O2CO3 material and the ZnCdS precursor solution are uniformly mixed, then solvent thermal reaction is carried out, after the reaction is completed, the temperature is cooled to room temperature, the precipitate is collected, and washing and drying treatment are carried out, so that the ZnCdS / La2O2CO3 composite photocatalytic material is obtained. The absorption and utilization efficiency of the ZnCdS / La2O2CO3 composite photocatalytic material prepared by the application to sunlight is greatly improved, and the photocatalytic water decomposition hydrogen production performance is significantly better than that of single ZnCdS and single La2O2CO3 material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of photocatalytic materials technology, and more specifically, to a ZnCdS / La2O2CO3 composite photocatalytic material and its preparation method. Background Technology

[0002] With the continuous advancement of industrialization and rapid economic development, the consumption of fossil fuels is accelerating, leading to a series of irreversible environmental problems, including global warming, ozone layer depletion, and acid rain. To promote sustainable social development, various clean and renewable energy sources, such as solar, wind, biomass, and hydrogen energy, have been developed. Among these, hydrogen energy, due to its high energy density and pollution-free combustion products, is considered one of the ideal alternatives to fossil fuels. Of the many hydrogen production technologies, photocatalytic water splitting, which directly utilizes solar energy to decompose water into hydrogen, is considered one of the most promising green hydrogen production methods.

[0003] Among visible-light-responsive photocatalytic materials, ZnCdS has become an important research target in the field of photocatalytic hydrogen production due to its suitable band gap and relatively mild preparation conditions. However, existing ZnCdS still suffers from limited hydrogen production efficiency and insufficient stability in practical photocatalytic hydrogen production applications, making it difficult to meet the needs of real-world applications. To address this, researchers have attempted to modify ZnCdS through various methods such as elemental doping, morphology control, and composite with other materials, aiming to obtain ZnCdS-based composite photocatalytic materials that possess both high photocatalytic activity and good stability. Nevertheless, the reported ZnCdS-based photocatalytic material systems are still relatively limited, and developing novel ZnCdS-based composite photocatalytic materials with excellent photocatalytic hydrogen production performance remains an important research topic of value in this field. Summary of the Invention

[0004] The problem addressed by this invention is: how to obtain novel ZnCdS-based composite photocatalytic materials with excellent photocatalytic hydrogen production performance.

[0005] To address the above problems, this invention provides a method for preparing a ZnCdS / La2O2CO3 composite photocatalytic material, comprising: Step S1: Prepare La2O2CO3 material and ZnCdS precursor solution; Step S2: After the La2O2CO3 material and the ZnCdS precursor solution are mixed evenly, a solvothermal reaction is carried out. After the reaction is completed, the mixture is cooled to room temperature, the precipitate is collected, washed and dried to obtain the ZnCdS / La2O2CO3 composite photocatalytic material.

[0006] Optionally, in step S2, the temperature of the solvothermal reaction is 180°C to 200°C, and the time is 12h to 15h.

[0007] Optionally, in step S2, the drying process is carried out at a temperature of 60°C to 80°C for a time of 12 hours to 24 hours.

[0008] Optionally, the preparation method of the La2O2CO3 material includes: Lanthanum nitrate is dissolved in water to obtain solution A; ammonium bicarbonate is dissolved in water to obtain solution B. After mixing solution A and solution B evenly, the mixture was allowed to stand, and the white precipitate was collected. The precipitate was then centrifuged, washed, and vacuum dried to obtain the La2O2CO3 precursor. The La2O2CO3 precursor was calcined to obtain the La2O2CO3 material.

[0009] Optionally, the calcination temperature is 500°C to 600°C, and the time is 4 hours to 5 hours.

[0010] Optionally, in solution A, the mass ratio of lanthanum nitrate to water is (1.3 to 1.4):(190 to 220); in solution B, the mass ratio of ammonium bicarbonate to water is (0.7 to 0.8):(190 to 220).

[0011] Optionally, the settling time is 10 to 16 hours.

[0012] Optionally, the method for preparing the ZnCdS precursor solution includes: mixing zinc acetate, cadmium acetate, L-cysteine ​​and triethylene glycol evenly to obtain the ZnCdS precursor solution.

[0013] Optionally, in the ZnCdS precursor solution, the mass ratio of zinc acetate, cadmium acetate, and L-cysteine ​​is (2 to 3): (3 to 4): (4 to 5).

[0014] The present invention also provides a ZnCdS / La2O2CO3 composite photocatalytic material, which is prepared by the method described above for preparing ZnCdS / La2O2CO3 composite photocatalytic material.

[0015] Compared with related technologies, this invention successfully prepared a ZnCdS / La2O2CO3 composite photocatalytic material by combining ZnCdS with La2O2CO3. Specifically, this invention uses a solvothermal method to grow a ZnCdS precursor in situ on the surface of La2O2CO3. In the resulting composite material, particulate ZnCdS is uniformly distributed on the surface of nanoflower-like La2O2CO3, and the two components form a close contact at the interface, constructing a band-matched heterojunction structure. Under simulated sunlight irradiation, this heterojunction structure can generate a built-in electric field at the interface, driving the directional transfer of photogenerated electrons and holes along a specific direction, effectively suppressing the recombination of photogenerated carriers, and significantly improving the utilization rate and lifetime of photogenerated electrons. At the same time, the unique 4f electron structure, oxygen storage capacity, and alkaline surface of La2O2CO3 provide abundant active sites for the reaction, further promoting the adsorption and activation of reactants on the catalyst surface. The synergistic effect of the above-mentioned multiple factors has significantly improved the absorption and utilization efficiency of sunlight by the ZnCdS / La2O2CO3 composite photocatalytic material prepared in this invention. Its photocatalytic water splitting hydrogen production performance is significantly better than that of single ZnCdS and single La2O2CO3 materials, providing a practical and feasible technical path for developing efficient and stable new photocatalytic hydrogen production materials. Attached Figure Description

[0016] Figure 1 The XRD comparison diagrams are of the ZnCdS / La2O2CO3 composite photocatalyst material prepared in Example 2, the La2O2CO3 photocatalyst material prepared in Comparative Example 1, and the ZnCdS solid solution photocatalyst material prepared in Comparative Example 2. Figure 2 The images show a comparison of the scanning electron microscope (SEM) morphologies of the ZnCdS / La2O2CO3 composite photocatalyst material prepared in Example 2, the La2O2CO3 photocatalyst material prepared in Comparative Example 1, and the ZnCdS solid solution photocatalyst material prepared in Comparative Example 2. Figure 3 The graph shows a comparison of the hydrogen production performance of the photocatalytic materials in Examples 1 to 4 and Comparative Examples 1 to 3. Detailed Implementation

[0017] To make the above-mentioned objects, features, and advantages of the present invention more apparent and understandable, specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings. Although some embodiments of the present invention are shown in the drawings, it should be understood that the present invention can be implemented in various forms and should not be construed as limited to the embodiments set forth herein. Rather, these embodiments are provided to provide a more thorough and complete understanding of the present invention. It should be understood that the accompanying drawings and embodiments of the present invention are for illustrative purposes only and are not intended to limit the scope of protection of the present invention.

[0018] Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to be limiting of the invention.

[0019] As used herein, the term "comprising" and its variations are open-ended inclusion, meaning "including but not limited to"; the term "based on" means "at least partially based on"; and in the description of this invention, unless otherwise stated, "a plurality of" means two or more.

[0020] This invention provides a method for preparing a ZnCdS / La2O2CO3 composite photocatalytic material, comprising: Step S1: Prepare La2O2CO3 material and ZnCdS precursor solution; Step S2: After the La2O2CO3 material and the ZnCdS precursor solution are mixed evenly, a solvothermal reaction is carried out. After the reaction is completed, the mixture is cooled to room temperature, the precipitate is collected, washed and dried to obtain the ZnCdS / La2O2CO3 composite photocatalytic material.

[0021] This invention successfully prepared a ZnCdS / La2O2CO3 composite photocatalytic material by combining ZnCdS with La2O2CO3. Specifically, this invention employs a solvothermal method to grow a ZnCdS precursor in situ on the surface of La2O2CO3. In the resulting composite material, particulate ZnCdS is uniformly distributed on the surface of nanoflower-like La2O2CO3, and the two components form a tight contact at the interface, constructing a band-matched heterojunction structure. Under simulated sunlight irradiation, this heterojunction structure can generate a built-in electric field at the interface, driving the directional transfer of photogenerated electrons and holes along specific directions, effectively suppressing the recombination of photogenerated carriers, and significantly improving the utilization rate and lifetime of photogenerated electrons. Simultaneously, the unique 4f electron structure, oxygen storage capacity, and alkaline surface of La2O2CO3 provide abundant active sites for the reaction, further promoting the adsorption and activation of reactants on the catalyst surface. The synergistic effect of the above-mentioned multiple factors has significantly improved the absorption and utilization efficiency of sunlight by the ZnCdS / La2O2CO3 composite photocatalytic material prepared in the embodiments of the present invention. Its photocatalytic water splitting hydrogen production performance is significantly better than that of single ZnCdS and single La2O2CO3 materials, providing a practical and feasible technical path for developing efficient and stable new photocatalytic hydrogen production materials.

[0022] In some embodiments of the present invention, in step S2, the temperature of the solvothermal reaction is 180°C to 200°C, and the time is 12h to 15h. In this embodiment, by controlling the temperature and time of the solvothermal reaction, it is possible to obtain a ZnCdS / La2O2CO3 composite material with good dispersibility and appropriate particle size while ensuring the crystallinity of the product. This is beneficial for exposing more photocatalytic active sites, thereby improving the photocatalytic hydrogen production performance.

[0023] In some embodiments of the present invention, in step S2, the drying temperature is 60°C to 80°C, and the time is 12h to 24h. The drying temperature of 60°C to 80°C is a mild low-temperature drying condition, which is far below the threshold at which ZnCdS and La2O2CO3 may undergo phase transformation or thermal decomposition. This effectively avoids material sintering, crystal phase transformation, or deactivation of surface active sites caused by local overheating during the drying process.

[0024] In some embodiments of the present invention, the preparation method of the La2O2CO3 material includes: Lanthanum nitrate is dissolved in water to obtain solution A; ammonium bicarbonate is dissolved in water to obtain solution B. After mixing solution A and solution B evenly, the mixture was allowed to stand, and the white precipitate was collected. The precipitate was then centrifuged, washed, and vacuum dried to obtain the La2O2CO3 precursor. The La2O2CO3 precursor was calcined to obtain the La2O2CO3 material.

[0025] This preparation method employs a co-precipitation approach combined with subsequent calcination. Lanthanum nitrate and ammonium bicarbonate are mixed in an aqueous solution to undergo a precipitation reaction, generating a lanthanum carbonate hydroxide precursor. Static treatment allows the precipitation reaction to proceed fully. Centrifugation and washing remove excess nitrate and ammonium ions, and vacuum drying yields a pure precursor powder. The subsequent calcination step transforms the precursor into well-crystallized La₂O₂CO₃ under controlled heat treatment conditions. This method is simple, uses readily available raw materials, and operates under mild conditions, producing high-purity, well-crystallized La₂O₂CO₃ material. This provides a structurally stable substrate for subsequent composite with ZnCdS, while avoiding the interference of impurities that might be introduced by complex synthetic routes.

[0026] In some embodiments of the present invention, the calcination temperature is 500°C to 600°C, and the time is 4 to 5 hours. The calcination temperature of 500°C to 600°C is within the suitable temperature range required for the formation of La2O2CO3, ensuring that the precursor fully decomposes and transforms into the target crystalline phase, while avoiding excessive sintering and growth of La2O2CO3 grains, a sharp decrease in specific surface area, or unnecessary phase transformations caused by excessively high temperatures. The holding time of 4 to 5 hours provides sufficient reaction time for phase transformation and thermal diffusion, ensuring complete transformation of the precursor into La2O2CO3.

[0027] In some embodiments of the present invention, in solution A, the mass ratio of lanthanum nitrate to water is (1.3 to 1.4):(190 to 220); in solution B, the mass ratio of ammonium bicarbonate to water is (0.7 to 0.8):(190 to 220).

[0028] In some embodiments of the present invention, the settling time is 10 hours to 16 hours.

[0029] In some embodiments of the present invention, the preparation method of the ZnCdS precursor solution includes: mixing zinc acetate, cadmium acetate, L-cysteine, and triethylene glycol uniformly to obtain the ZnCdS precursor solution. In this preparation method, zinc acetate and cadmium acetate are used as zinc and cadmium sources, respectively, L-cysteine ​​acts as both a sulfur source and a ligand, and triethylene glycol is used as a polyol solvent. The thiol and amino groups in the L-cysteine ​​molecule can react with Zn... 2+ Cd 2+ Coordination occurs, forming a uniformly dispersed metal-ligand complex precursor in the triethylene glycol medium, preventing the direct formation of sulfide precipitates by metal ions before heating. This precursor solution preparation method maintains a homogeneous and stable system before the solvothermal reaction begins, premixing zinc, cadmium, and sulfur at the molecular level. This creates a favorable chemical environment for the subsequent formation of a homogeneous ZnCdS solid solution and its in-situ growth on the La2O2CO3 surface during the solvothermal reaction.

[0030] In some embodiments of the present invention, the mass ratio of zinc acetate, cadmium acetate, and L-cysteine ​​in the ZnCdS precursor solution is (2 to 3): (3 to 4): (4 to 5).

[0031] The present invention also provides a ZnCdS / La2O2CO3 composite photocatalytic material, which is prepared by the method described above for preparing ZnCdS / La2O2CO3 composite photocatalytic material.

[0032] The present invention will be further described below with reference to specific embodiments.

[0033] Example 1 A1. Dissolve 1.39g of lanthanum nitrate in 200g of water to obtain solution A; dissolve 0.75g of ammonium bicarbonate in 200g of water to obtain solution B; mix solution A and solution B evenly, let stand for 12h, and collect the white precipitate; wash the white precipitate three times with deionized water by centrifugation, then wash it twice with anhydrous ethanol by centrifugation, and then vacuum dry it at 80℃ for 12h to obtain the La2O2CO3 precursor.

[0034] A2. The La2O2CO3 precursor is calcined to obtain La2O2CO3 material; wherein the calcination temperature is 550℃ and the time is 4h.

[0035] A3. Add 27.4 mg zinc acetate, 33.3 mg cadmium acetate and 45.4 mg L-cysteine ​​to 30 mL triethylene glycol and mix well to obtain a ZnCdS precursor solution. A4. Add the La2O2CO3 material obtained in step A2 (preset mass) to the ZnCdS precursor solution obtained in step A3, mix thoroughly, and carry out a solvothermal reaction. After the reaction is complete, cool to room temperature and collect the precipitate. Wash the precipitate five times each with deionized water and anhydrous ethanol, and then vacuum dry at 80°C for 12 hours to obtain the ZnCdS / La2O2CO3 composite photocatalytic material. The preset mass is 10 mg, and the solvothermal reaction temperature is 200°C for 14 hours.

[0036] Example 2 The difference from Example 1 is that in step A4, the preset mass is 20mg.

[0037] Example 3 The difference from Example 1 is that in step A4, the preset mass is 30mg.

[0038] Example 4 The difference from Example 1 is that in step A4, the preset mass is 40mg.

[0039] Example 5 A1. Dissolve 1.3g of lanthanum nitrate in 200g of water to obtain solution A; dissolve 0.7g of ammonium bicarbonate in 200g of water to obtain solution B; mix solution A and solution B evenly, let stand for 12h, and collect the white precipitate; wash the white precipitate three times with deionized water by centrifugation, then wash it twice with anhydrous ethanol by centrifugation, and then vacuum dry it at 80℃ for 12h to obtain the La2O2CO3 precursor.

[0040] A2. The La2O2CO3 precursor is calcined to obtain La2O2CO3 material; wherein the calcination temperature is 500℃ and the time is 5h.

[0041] A3. Add 27.4 mg zinc acetate, 33.3 mg cadmium acetate and 45.4 mg L-cysteine ​​to 30 mL triethylene glycol and mix well to obtain a ZnCdS precursor solution. A4. Add the La2O2CO3 material obtained in step A2 (preset mass) to the ZnCdS precursor solution obtained in step A3, mix thoroughly, and carry out a solvothermal reaction. After the reaction is complete, cool to room temperature and collect the precipitate. Wash the precipitate five times each with deionized water and anhydrous ethanol, and then vacuum dry at 80°C for 12 hours to obtain the ZnCdS / La2O2CO3 composite photocatalytic material. The preset mass is 10 mg, and the solvothermal reaction temperature is 180°C for 15 hours.

[0042] Example 6 A1. Dissolve 1.4g of lanthanum nitrate in 200g of water to obtain solution A; dissolve 0.8g of ammonium bicarbonate in 200g of water to obtain solution B; mix solution A and solution B evenly, let stand for 12h, and collect the white precipitate; wash the white precipitate three times with deionized water by centrifugation, then wash it twice with anhydrous ethanol by centrifugation, and then vacuum dry it at 80℃ for 12h to obtain the La2O2CO3 precursor.

[0043] A2. The La2O2CO3 precursor is calcined to obtain La2O2CO3 material; wherein the calcination temperature is 600℃ and the time is 4h.

[0044] A3. Add 27.4 mg zinc acetate, 33.3 mg cadmium acetate and 45.4 mg L-cysteine ​​to 30 mL triethylene glycol and mix well to obtain a ZnCdS precursor solution. A4. Add the La2O2CO3 material obtained in step A2 (preset mass) to the ZnCdS precursor solution obtained in step A3, mix thoroughly, and carry out a solvothermal reaction. After the reaction is complete, cool to room temperature and collect the precipitate. Wash the precipitate five times each with deionized water and anhydrous ethanol, and then vacuum dry at 80°C for 12 hours to obtain the ZnCdS / La2O2CO3 composite photocatalytic material. The preset mass is 10 mg, and the solvothermal reaction temperature is 200°C for 12 hours.

[0045] Comparative Example 1 1.39 g of lanthanum nitrate was dissolved in 200 g of water to obtain solution A; 0.75 g of ammonium bicarbonate was dissolved in 200 g of water to obtain solution B; solution A and solution B were mixed evenly and allowed to stand for 12 h, and a white precipitate was collected; the white precipitate was first washed three times by centrifugation with deionized water, then washed twice by centrifugation with anhydrous ethanol, and then vacuum dried at 80 °C for 12 h to obtain the La2O2CO3 precursor.

[0046] The La2O2CO3 precursor was calcined to obtain the La2O2CO3 photocatalytic material; wherein the calcination temperature was 550℃ and the time was 4h.

[0047] Comparative Example 2 27.4 mg zinc acetate, 33.3 mg cadmium acetate, and 45.4 mg L-cysteine ​​were added to 30 ml triethylene glycol and mixed thoroughly to obtain a ZnCdS precursor solution. The ZnCdS precursor solution was subjected to a solvothermal reaction. After the reaction was completed, the mixture was cooled to room temperature and the precipitate was collected. The precipitate was washed five times each with deionized water and anhydrous ethanol by centrifugation, and then vacuum dried at 80 °C for 12 h to obtain a ZnCdS solid solution photocatalytic material. The solvothermal reaction was carried out at 200 °C for 12 h.

[0048] Comparative Example 3 1.39 g of lanthanum nitrate was dissolved in 200 g of water to obtain solution A; 0.75 g of ammonium bicarbonate was dissolved in 200 g of water to obtain solution B; solution A and solution B were mixed evenly and allowed to stand for 12 h, and a white precipitate was collected; the white precipitate was first washed three times by centrifugation with deionized water, then washed twice by centrifugation with anhydrous ethanol, and then vacuum dried at 80 °C for 12 h to obtain the La2O2CO3 precursor.

[0049] The La2O2CO3 precursor was calcined to obtain the La2O2CO3 photocatalytic material; wherein the calcination temperature was 550℃ and the time was 4h.

[0050] 27.4 mg zinc acetate, 33.3 mg cadmium acetate, and 45.4 mg L-cysteine ​​were added to 30 ml triethylene glycol and mixed thoroughly to obtain a ZnCdS precursor solution. The ZnCdS precursor solution was subjected to a solvothermal reaction. After the reaction was completed, the mixture was cooled to room temperature and the precipitate was collected. The precipitate was washed five times each with deionized water and anhydrous ethanol by centrifugation, and then vacuum dried at 80 °C for 12 h to obtain a ZnCdS solid solution photocatalytic material. The solvothermal reaction was carried out at 200 °C for 12 h.

[0051] 10 mg of La2O2CO3 photocatalyst material and 10 mg of ZnCdS solid solution photocatalyst material were ground and mixed evenly to obtain a composite photocatalyst material.

[0052] Effect Example The ZnCdS / La2O2CO3 composite photocatalyst material prepared in Example 2, the La2O2CO3 photocatalyst material prepared in Comparative Example 1, and the ZnCdS solid solution photocatalyst material prepared in Comparative Example 2 were characterized by XRD. The results are shown in the figure. Figure 1 . Figure 1 The three curves, from top to bottom, represent the XRD diffraction patterns of the ZnCdS / La2O2CO3 composite photocatalyst, the La2O2CO3 photocatalyst, and the ZnCdS solid solution photocatalyst. From... Figure 1 It can be seen that the characteristic diffraction peaks of ZnCdS and La2O2CO3 appear simultaneously in the ZnCdS / La2O2CO3 composite photocatalyst material prepared in Example 2, indicating that the crystal structure and crystal integrity of the two are maintained after compositing, and the La2O2CO3 and ZnCdS solid solutions are combined together in the ZnCdS / La2O2CO3 composite photocatalyst material.

[0053] The ZnCdS / La2O2CO3 composite photocatalyst material prepared in Example 2, the La2O2CO3 photocatalyst material prepared in Comparative Example 1, and the ZnCdS solid solution photocatalyst material prepared in Comparative Example 2 were characterized by scanning electron microscopy. The results are shown in the figure. Figure 2 . Figure 2 Image (a) is a SEM image of the ZnCdS solid solution photocatalytic material. Figure 2 Image (b) is a SEM image of the La2O2CO3 photocatalyst material. Figure 2 Image (c) shows a SEM image of the ZnCdS / La2O2CO3 composite photocatalyst. From... Figure 2 As can be seen in (a), the ZnCdS solid solution photocatalytic material prepared in Comparative Example 2 is granular; from Figure 2 As can be seen in Figure (b), the La2O2CO3 photocatalytic material prepared in Comparative Example 1 has a nanoflower-like structure; from Figure 2 As can be seen in (c), in Example 2, the particulate ZnCdS solid solution was successfully grown on the nanoflower-like La2O2CO3, forming a ZnCdS / La2O2CO3 composite photocatalytic material.

[0054] Ten mg of each of the ZnCdS / La2O2CO3 composite photocatalyst material prepared in Examples 1 to 4, the La2O2CO3 photocatalyst material in Comparative Example 1, the ZnCdS solid solution photocatalyst material prepared in Comparative Example 2, and the composite photocatalyst material prepared in Comparative Example 3 were uniformly dispersed in 50 mL of water. Using sodium sulfide and sodium sulfite as sacrificial agents, a photocatalytic water splitting experiment to produce hydrogen was conducted at 5°C. Every hour, the generated hydrogen was quantitatively analyzed and detected by gas chromatography. The results are shown in [Figure number missing]. Figure 3 . Figure 3 In this context, the La2O2CO3 series corresponds to the detection results of the La2O2CO3 photocatalytic material in Example 1, the ZnCdS series corresponds to the detection results of the ZnCdS solid solution photocatalytic material, the ZnCdS / La2O2CO3-physical mixture series corresponds to the detection results of the composite photocatalytic material prepared in Example 3, and the ZnCdS / La2O2CO3-1 to ZnCdS / La2O2CO3-4 series correspond to the detection results of the ZnCdS / La2O2CO3 composite photocatalytic materials prepared in Examples 1 to 4, respectively. Figure 3 It can be seen that, compared with Comparative Examples 1 to 3, the photocatalytic materials prepared in Examples 1 to 4 have higher hydrogen production, indicating that the ZnCdS / La2O2CO3 composite photocatalytic materials prepared in Examples 1 to 4 have better photocatalytic hydrogen production performance.

[0055] While the present invention has been disclosed above, its scope of protection is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and all such changes and modifications will fall within the scope of protection of the present invention.

Claims

1. A method for preparing a ZnCdS / La2O2CO3 composite photocatalytic material, characterized in that, include: Step S1: Prepare La2O2CO3 material and ZnCdS precursor solution; Step S2: After the La2O2CO3 material and the ZnCdS precursor solution are mixed evenly, a solvothermal reaction is carried out. After the reaction is completed, the mixture is cooled to room temperature, the precipitate is collected, washed and dried to obtain the ZnCdS / La2O2CO3 composite photocatalytic material.

2. The preparation method of the ZnCdS / La2O2CO3 composite photocatalytic material according to claim 1, characterized in that, In step S2, the temperature of the solvothermal reaction is 180°C to 200°C, and the time is 12h to 15h.

3. The preparation method of the ZnCdS / La2O2CO3 composite photocatalytic material according to claim 1, characterized in that, In step S2, the drying process is carried out at a temperature of 60°C to 80°C for 12 hours to 24 hours.

4. The preparation method of the ZnCdS / La2O2CO3 composite photocatalytic material according to claim 1, characterized in that, The preparation method of the La2O2CO3 material includes: Lanthanum nitrate is dissolved in water to obtain solution A; ammonium bicarbonate is dissolved in water to obtain solution B. After mixing solution A and solution B evenly, the mixture was allowed to stand, and the white precipitate was collected. The precipitate was then centrifuged, washed, and vacuum dried to obtain the La2O2CO3 precursor. The La2O2CO3 precursor was calcined to obtain the La2O2CO3 material.

5. The preparation method of the ZnCdS / La2O2CO3 composite photocatalytic material according to claim 4, characterized in that, The calcination temperature is 500℃ to 600℃, and the time is 4h to 5h.

6. The preparation method of the ZnCdS / La2O2CO3 composite photocatalytic material according to claim 4, characterized in that, In solution A, the mass ratio of lanthanum nitrate to water is (1.3 to 1.4):(190 to 220); in solution B, the mass ratio of ammonium bicarbonate to water is (0.7 to 0.8):(190 to 220).

7. The preparation method of the ZnCdS / La2O2CO3 composite photocatalytic material according to claim 4, characterized in that, The settling time is 10 to 16 hours.

8. The preparation method of the ZnCdS / La2O2CO3 composite photocatalytic material according to claim 1, characterized in that, The method for preparing the ZnCdS precursor solution includes: mixing zinc acetate, cadmium acetate, L-cysteine ​​and triethylene glycol evenly to obtain the ZnCdS precursor solution.

9. The preparation method of the ZnCdS / La2O2CO3 composite photocatalytic material according to claim 8, characterized in that, In the ZnCdS precursor solution, the mass ratio of zinc acetate, cadmium acetate, and L-cysteine ​​is (2 to 3): (3 to 4): (4 to 5).

10. A ZnCdS / La2O2CO3 composite photocatalytic material, characterized in that, The ZnCdS / La2O2CO3 composite photocatalyst material was prepared using the method described in any one of claims 1 to 9.